Evaluation of non-carcass components of goat grazing in Caatinga rangeland supplemented with spineless cactus and native plants - Silva, Dulciene Karla de Andrade; Cordeiro, Fábia Simone Bezerra; Cardoso, Daniel Barros; Magalhães, André Luiz Rodrigues; Melo, Airon Aparecido Silva de; Pereira, Kedes Paulo (Acta Scientiarum. Animal Sciences, 2020)
The objective of this study was to evaluate non-carcass components of goats submitted to grazing in the Caatinga rangeland and supplemented with spineless cactus (Nopalea cochelinifera Salm Dick), Jitirana hay (Merremia aegyptia L. Urban) and Mororó hay (Bauhinia cheilanta Bong Stend). Thirty male goats (castrated), with no defined breed, with an initial mean body weight of 19 ± 0.35 kg and approximately 90 days of age were used. The treatments consisted of grazing without supplementation (GWS), grazing + Jitirana hay (GJ); grazing + Jitirana hay + spineless cactus (GJSC); grazing + Mororó hay (GM); grazing + Mororó hay + spineless cactus (GMSC). The means of the variables were tested by Tukey’s test at 5% probability. The goats fed GWS, GJSC, GM and GMSC presented higher weights and yields of the diaphragm, and the spleen weight (p < 0.05). The highest yield of omasum (p < 0.05) occurred with goats fed GJ treatment. There were treatments (p < 0.05) on omental fat weight and leg yield, with the highest values for goats, fed GWS, GJSC, GM, and GMSC. The "Buchada" EBW-1 yield was higher (p < 0.05) for animals fed GWS. Feeding supplementation of goats grazing in the Caatinga had few influences on weights and yields of non-carcass components.